Daya Terima Dan Nilai Gizi Oral Nutritional Supplement (ONS) Modifikasi Smoothie Modisco Berbasis Susu Kedelai Dan Buah Sebagai Alternatif Penanganan Anak Gizi Kurang - Bhaskara Kurni (Health Care Media, 2024)
The aim of the research is to analyze the acceptability and nutritional value of Oral Nutritional Supplement (ONS) Modified Modisco Smoothie based on soy milk and fruit as an alternative for treating malnourished children. The research method used was a pure experimental method with a completely randomized design with 3 repetitions. The treatment carried out was the addition of different fruits such as strawberries, bananas and avocados. The tests carried out were energy, protein, fat, potassium and magnesium. Potassium and magnesium data were analyzed using Anova. Receptivity testing using the hedonic method and analyzed using Repeated Measure. The results of this research are that the nutrients per 100 grams of energy smoothie range from 159.86 to 236.6 calories, protein 5.0 to 5.8 grams, fat 6.5 to 15.7 grams. Average potassium levels are between 995.6 to 1063 ppm and average magnesium levels are between 704.6 to 958 ppm. The addition of fruit increases preferences in terms of color, aroma, taste and texture. In fact, the addition of the most preferred fruit is strawberries. This research can be concluded that the nutritional value of Modisco smoothies with the addition of fruit (banana, avocado and strawberries) has energy, protein and fat values ​​that exceed Modisco standards. The addition of strawberries was chosen because it has high nutritional value and the most acceptable acceptability. Modisco, a type of oral nutrition supplement (ONS), shows effectiveness in improving children's nutritional status.